An application of IPA approach on the optimization of a mining port stockyard system - Ayu, Media Anugerah; Cardew-Hall, Michael (2002)
In this research a stockyard system of a mining operation was analyzed using backward analysis. The system was decomposed into two sub-systems : sub-system 1 modelled the outflow from the stockyard and sub-system 2 which show the inflow. Perturbation Analysis Robbins Monro Single Run (PARMSR) algorithm were applied in the optimization of sub-system 1 and rules devised to determining optimal operating condition in sub-system 2. The results show that PARMSR algorithm applying IPA can be used to estimate the optimal cost function in subsystem 1 with a high level of confidence. Using the result from sub-system 1, sub-system 2 was analyzed based on rules devised to obtain an overall optimal result of the stockyard system. The overall results can be used to build an optimal operating management strategy of a stockyard system of a mining operation at certain set of stockyard capacity.